Investigation on the Effect of Different Tillage Machineries on the Physical Properties of Soil and Yield of Upland Paddy - Singh, V.K.; Alam, S.M; Sinha, A.K. (Journal of Soil and Water Conservation, 2022)
Preparation of good seed bed is one of the most important factor which determines the yield of any crop. The quality of seedbed is judged by its tilth, a term coined to describe the physical condition of the field relative to its response to tillage machineries and its mechanical impedence to root penetration. Tilth is the outcome of a complex phenomenon of soil-air-water relationship and is difficult to measure directly. Generally it is judged by different associated physical' properties of soil like, porosity, bulk density, compaction etc., which determines the suitability of a seedbed from the point of view of seed emergence and plant growth (yoder 1937); Bayer (1956). To obtain best result various types of machineries like different types of ploughs, harrows etc. alone as well as in combination are being used, but all are situation oriented and have been found to affect soil properties variously (Khan (1953); Khan et. al (1958); Dospokhov and Bolobolova (1959); Latsen (1963) and Mohsin (1964). This is an important aspect and needs fully consideration and investigation.